The oldest known priapulid‐like scalidophoran animal and its implications for the early evolution of cycloneuralians and ecdysozoans. Issue 3 (23rd April 2014) - Liu, Yunhuan; Xiao, Shuhai; Shao, Tiequan; Broce, Jesse; Zhang, Huaqiao
SUMMARY Morphological phylogenetic analyses suggest that scalidophorans (priapulids, loriciferans, and kinorhynchs) and nematoids (nematodes and nematomorphs) form the ecdysozoan clade Cycloneuralia, which is a sister group to panarthropods. It has been proposed that extant priapulids and Cambrian priapulid‐like scalidophorans, because of their conserved evolution, have the potential to illuminate the ancestral morphology, ecology, and developmental biology of highly derived ecdysozoans such as nematods and arthropods. As such, Cambrian fossils, particularly Markuelia and possibly olivooids, can inform the early evolution of scalidophorans, cycloneuralians, and ecdysozoans. However, the scalidophoran Markuelia is known exclusively as embryo fossils, and the olivooids have been alternatively interpreted as cnidarians or cycloneuralians. Here, we describe a post‐embryonic scalidophoran fossil Eopriapulites sphinx new genus and species, which represents the oldest known scalidophoran, from the early Cambrian Period (∼535 Ma) in South China. E. sphinx is similar to modern scalidophorans in having an introvert armed with hollow scalids, a collar with coronal scalids, and a pharynx with pharyngeal teeth, but its scalids and pharyngeal teeth are arranged in a hexaradial pattern. Phylogenetically resolved as a stem‐group scalidophoran, E. sphinx shares a hexaradial pattern with the hexaradial arrangement of certain anatomical structures in kinorhynchs, loriciferans, nematoids, and Cambrian fossils such as Eolympia pediculata, which could also be a scalidophoran. Thus, the bodyplan of ancestral cycloneuralians may have had a component of hexaradial symmetry (i.e., some but not necessarily all anatomical parts are hexaradially arranged). If panarthropods are nested within paraphyletic cycloneuralians, as several molecular phylogenetic analyses suggest, the ancestral ecdysozoans may have been a legless worm possibly with a component of hexaradial symmetry.